Assessment of Nurses’ knowledge about Neonatal Continuous Positive Airway Pressure (CPAP) Nasal Injuries at Neonatal Intensive Care Unit - Ali Jawad Hameed Helal, Zahid Jasim Mohammed, Afifa Radha Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the most unpleasant and painful NCPAP related complication is the risk of nasal skin breakdown. It commonly occurs on areas under high pressure of nasal interface, mostly on the nasal bridge but can take place at any area under pressure of mask or prong which are used to connect the ventilation system to the patient’s nose. Objective: Evaluation of nurses’ knowledge about Neonatal Continuous Positive Airway Pressure (CPAP) Nasal Injuries at Neonatal Intensive Care Unit. Methodology: A Descriptive cross-sectional study, quantitative research has been carried throughout the present study to evaluate their management about nasal injury related to CPAP at neonates’ intensive care units in hospitals of Medical City director in Baghdad and it examined the type of relationship between variables. During the period from 3rd October 2021 to 15th May 2022. Results of the study: Results that observed responses of high evaluated generally assigned, and they are accounted 27(81.82%) items, while leftover items were a assigned moderate evaluation 5(15.15%), and low evaluation 1(3.03%). Conclusion: In concerning nursing management about neonatal continuous positive airway pressure (CPAP) nasal injuries at neonatal intensive care unit are assigned at the established level in which that achieving goal of this study. Recommendations: Training courses to increase nurses’ knowledge and practices about working on the continuous positive air pressure device.